Samsung Smartphone Purchasing Decisions Based on Lifestyle, Product Quality, and Brand Image Among Samsung Consumers in Sukoharjo Regency - Rama Marhanda; Istiqomah Istiqomah; Supawi Pawenang (Economos : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to determine the influence of lifestyle, product quality, and brand image on Samsung smartphone purchase decisions in Sukoharjo Regency. This research employs a descriptive quantitative design. The population in this study consists of consumers who use or purchase Samsung smartphones in Sukoharjo Regency, which is infinite in number, and the sample used was 100 respondents. The sampling technique used non-probability sampling with purposive sampling method. Data were obtained through questionnaire distribution to respondents who met the criteria. Data analysis included classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, F test, hypothesis testing (t test), and coefficient of determination test (R²). The results of this study indicate that the lifestyle variable has a significant positive effect on purchase decisions. Product quality has no significant effect on purchase decisions. Brand image has a significant positive effect on purchase decisions. Based on the coefficient of determination (R²) test results, the variables of Lifestyle, Product Quality, and Brand Image contribute 54.3% to Purchase Decisions, while the remaining 45.7% is influenced by other factors outside this research model.